Texts of the Tokyo round agreements (GATT GenevaCH, 1986)
Contains texts of six agreements on the following; technical barriers to trade; government procurement; interpretation and application of articles vi, xvi, and xxiii; implementation of article vii; import licensing procedures; implementation of article vi of GATT. Outlines three sectoral agreements viz. the arrangement regarding bovine meat; the international dairy arrangement; the agreement on trade in civil aircraft. Records four decisions of the contracting parties regarding differential and more favourable treatment, reciprocity, and fuller participation of developing countries; declaration on trade measures; safeguard action for development purposes and the undertakings regarding fortification, dispute settlement and surveillance.
DC